Respuesta :

Answer:

Option B) [tex]{\bf A-B}={\bf 5x}^{\bf 2}+{\bf 11x-13} [/tex]

Step-by-step explanation:

Given [tex]A=3x^2+5x-6[/tex]

          [tex]B=-2x^2-6x+7[/tex]

To find [tex]A-B[/tex]

[tex]A-B=3x^2+5x-6-(-2x^2-6x+7)[/tex]

[tex]A-B=3x^2+5x-6+2x^2+6x-7)[/tex]

[tex]A-B=5x^2+11x-13[/tex]

Option B) is correct

Answer:

IF A = 3x² + 5x - 6 and B = -2x² - 6x + 7 then A - B equal is

The correct option is B

5x² + 11x - 13

Step-by-step explanation:

Given:

A = 3x² + 5x - 6     and

B = -2x² - 6x + 7

To Find :

(A - B) = ?

Solution:

A = 3x² + 5x - 6    

B = -2x² - 6x + 7

Now,

( A -B ) = (3x² + 5x - 6 ) - (-2x² - 6x + 7 )

Now first minus sign will enter in the bracket ,

( - )×( - ) = +

( - )×( + ) = -

∴ ( A -B ) = (3x² + 5x - 6 )  + 2x² + 6x - 7

              = 3x² + 2x² + 5x + 6x  - 6 - 7

               =  5x² + 11x - 13

∴ (A - B ) = 5x² + 11x - 13

Therefore,

IF A = 3x² + 5x - 6 and B = -2x² - 6x + 7 then A - B equal is

The correct option is B

(A - B ) = 5x² + 11x - 13